Three-dimensional porous carbon-based iron selenide / sulfide composite material and application thereof in sodium ion batteries
Patent Information
- Application Number
- CN202311274379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-09-28
AI Technical Summary
但是,硫族化合物本征电子导电性差、动力学缓慢,在循环过程中体积膨胀大,导致结构发生破坏,储钠离子能力下降,因此严重阻碍其实际应用
[0026] This invention provides a three-dimensional porous carbon-based selenide/iron sulfide composite material. The successful construction of the three-dimensional porous carbon confined structure can effectively shorten the diffusion path, accelerate the kinetic reaction rate, improve electronic conductivity, and alleviate the volume expansion of chalcogenides, which is of great significance for providing stable, high-specific-capacity sodium-ion batteries.
Smart Images

Figure CN117334907B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery anode materials, specifically relating to a three-dimensional porous carbon-based selenide / iron sulfide composite material and its application in sodium-ion batteries. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] For decades, lithium-ion batteries (LIBs) have dominated the energy storage market due to their high energy and power density, long lifespan, and safety. However, high cost and the scarcity of lithium resources have hindered the further development of LIBs. Sodium-ion batteries (SIBs), as an environmentally friendly and resource-rich alternative, have become a focus of research. However, although SIBs share similar working principles with LIBs, conventional electrodes that are effective in LIBs may not be suitable for SIBs because sodium... + The radius is Li + 1.34 times that of Na + The insertion of [something] typically leads to sluggish battery dynamics and severe capacity degradation.
[0004] To alleviate the aforementioned problems, it is necessary to develop reversible, adaptable technology suitable for Na+. + Advanced electrode materials are essential. Chalcogenides generally exhibit better reversibility than oxides, and the metal-sulfur / selenium (MS / Se) bond is relatively weaker than the metal-oxygen (MO) bond, thus possessing more favorable kinetics and higher first-cycle coulombic efficiency. However, chalcogenides suffer from poor intrinsic electronic conductivity, slow kinetics, and significant volume expansion during cycling, leading to structural damage and a decrease in sodium ion storage capacity, thus severely hindering their practical application. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a sulfur-containing anode material with higher conductivity and rate performance. To achieve this objective, the present invention combines metallic sulfur compounds with carbonaceous materials, providing a three-dimensional porous carbon-based selenide / iron sulfide composite material. In this composite material, the confined carbon structure promotes Na... +It plays an important role in reversible storage: further combining metal sulfur compounds with carbon materials effectively shortens the ion diffusion path and creates highly accessible channels at the interface, which is beneficial to surface redox pseudocapacitance and interfacial intercalation pseudocapacitance, effectively suppressing the volume expansion of sulfur-containing anode materials, thereby obtaining sodium-ion batteries with high capacity and excellent cycle stability.
[0006] Based on the above-mentioned technical effects, the present invention provides the following solution:
[0007] In a first aspect, a three-dimensional porous carbon-based selenide / iron sulfide composite material is provided, comprising porous carbon nanoribbons, iron selenide, and iron sulfide; wherein the porous carbon nanoribbons are amorphous carbon materials that are interwoven to form a three-dimensional structure; and iron selenide and iron sulfide are distributed in the above-mentioned three-dimensional structure.
[0008] According to the scanning electron microscope results, in the above composite material, the interlaced carbon nanoribbons form a three-dimensional structure, and the metal particles are etched on the surface of the carbon nanoribbons to form abundant pores.
[0009] Secondly, a method for preparing the above-mentioned three-dimensional porous carbon-based selenide / iron sulfide composite material is provided, comprising the following steps:
[0010] S1. Add the graphene oxide solution to the sodium alginate solution and mix well to obtain a mixed solution;
[0011] S2. Add the mixed solution dropwise to the iron ion solution to form gel particles, collect the gel particles and dry them;
[0012] S3. The dried gel particles are subjected to sulfidation and selenization reactions in sequence to obtain the three-dimensional porous carbon-based selenide / iron sulfide composite material.
[0013] In step S1, the concentration of the graphene oxide solution is 75-135 g / L, the concentration of the sodium alginate solution is 18.75-37.5 g / L, and the two solutions are mixed at a volume ratio of 2-5:1 to obtain the above mixed solution.
[0014] In step S2, the iron ion solution is preferably a stable iron salt solution, such as ferric nitrate; the concentration of iron ions in the solution is preferably 1-3 mol / L; the iron ion solution should have a sufficient dosage to ensure complete support for the gel particles formed after the mixed solution is added, and the suitable volume of the iron ion solution is 1 to 3 times the volume of the mixed solution. Meanwhile, to ensure a more uniform distribution of iron in the gel particles, the iron ion solution can be continuously stirred at a low speed during the addition of the mixed solution.
[0015] In addition, the preferred drying method for the above-mentioned gel particles is a drying method that does not require heat treatment, such as freeze drying.
[0016] In step S3, the vulcanization reaction proceeds as follows:
[0017] The dried gel particles were mixed with sulfur powder at a mass ratio of 1:4-6 and then calcined at 450-550℃ for 2.5-3.5 hours under an inert atmosphere.
[0018] The selenization reaction is as follows:
[0019] The gel particles after the sulfidation reaction are mixed with selenium powder at a mass ratio of 1:1-3 and then calcined at 600-700℃ for 1.5-2.5 hours under an inert atmosphere.
[0020] The above-mentioned sulfidation and selenization reactions can be carried out using devices such as tube furnaces, where the mixed materials are placed in a quartz boat and heated according to the above-mentioned heating method.
[0021] Thirdly, the present invention provides the application of the three-dimensional porous carbon-based selenide / iron sulfide composite material as described in the first aspect in sodium-ion batteries.
[0022] In one embodiment verified by the present invention, the specific application is that the above-mentioned composite material is used to prepare the negative electrode of a sodium-ion battery.
[0023] Therefore, in a fourth aspect, the present invention provides a sodium-ion battery negative electrode sheet, which is formed by coating an electrode sheet with a three-dimensional porous carbon-based selenide / iron sulfide composite material, carboxymethyl cellulose and carbon black in a mass ratio of 7-9:0.8-1.2:0.8-1.2 as described in the first aspect.
[0024] Fifthly, a sodium-ion battery comprising a sodium-ion battery negative electrode as described in the fourth aspect.
[0025] The beneficial effects of one or more of the above technical solutions are as follows:
[0026] This invention provides a three-dimensional porous carbon-based selenide / iron sulfide composite material. The successful construction of the three-dimensional porous carbon confined structure can effectively shorten the diffusion path, accelerate the kinetic reaction rate, improve electronic conductivity, and alleviate the volume expansion of chalcogenides, which is of great significance for providing stable, high-specific-capacity sodium-ion batteries. Attached Figure Description
[0027] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0028] Figure 1 This is a scanning electron microscope image of the three-dimensional porous carbon-based selenide / iron sulfide composite material in Example 1;
[0029] Figure 2The image shows the cycling curve of the sodium-ion battery anode material with a three-dimensional porous carbon-based selenide / iron sulfide composite material structure in Example 1. Detailed Implementation
[0030] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0031] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0032] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0033] Example 1
[0034] This embodiment provides a method for preparing a three-dimensional porous carbon-based selenide / iron sulfide composite material, comprising the following steps:
[0035] 1. Solution A: Dissolve 1.5g of sodium alginate in 80ml of deionized water and stir for 3 hours at room temperature to ensure thorough mixing until a homogeneous solution with a certain viscosity is obtained.
[0036] 2. Solution B: Dissolve 200 mg of graphene oxide in 20 ml of deionized water and sonicate until uniformly dispersed;
[0037] 3. Mixed solution: Mix solution A and solution B at a volume ratio of 4:1 to obtain a mixed solution;
[0038] 4. Ferric nitrate solution: Prepare a 1 mol / L solution at room temperature. -1 200 mL of ferric nitrate solution was used to uniformly disperse iron ions by magnetic stirring.
[0039] 5. The mixed solution from step 3 is added dropwise to the ferric nitrate solution using a peristaltic pump, forming gel particles in the solution. During the dropwise addition of the mixed solution, the ferric nitrate solution is continuously stirred at a low speed with a magnetic force to ensure uniform dispersion of iron ions.
[0040] 6. Collect the gel particles, rinse them repeatedly with deionized water, freeze them in liquid nitrogen, and then transfer them to a freeze dryer for drying.
[0041] 7. Place the dried granules in a quartz boat, then transfer them to a tube furnace. Under inert gas protection, first sulfide and then selenide are applied. The sulfide treatment method is as follows:
[0042] In a nitrogen atmosphere, sulfur powder and dried granules were mixed at a mass ratio of 1:5 and placed in a quartz boat. The tube furnace was heated at a rate of 3℃ / min to 500℃ for 3 hours.
[0043] The selenization method is as follows: In an argon atmosphere, selenium powder is mixed with the above-mentioned sulfurized material at a mass ratio of 1:2. The heating rate of the tube furnace is 3℃ / min, and the temperature is raised to 650℃ for 2 hours. After the heating is completed, the material is naturally cooled to room temperature and removed to obtain the three-dimensional porous carbon-based selenized / sulfided iron composite material.
[0044] The obtained three-dimensional porous carbon-based selenide / iron sulfide composite material has the following morphology: Figure 1 As shown, the interlaced carbon nanoribbons form a three-dimensional structure, while the porous structure is formed by etching the metallic iron particles.
[0045] Example 2
[0046] This embodiment provides another method for preparing a three-dimensional porous carbon-based selenide / iron sulfide composite material, comprising the following steps:
[0047] 1. Solution A: Dissolve 2g of sodium alginate in 80ml of deionized water and stir for 3.5h at room temperature to ensure thorough mixing until a homogeneous solution with a certain viscosity is obtained.
[0048] 2. Solution B: Dissolve 300 mg of graphene oxide in 40 ml of deionized water and sonicate until uniformly dispersed;
[0049] 3. Mixed solution: Mix solution A and solution B at a volume ratio of 2:1 to obtain a mixed solution;
[0050] 4. Ferric nitrate solution: Prepare a 1.5 mol / L solution at room temperature. -1 200 mL of ferric nitrate solution was used to uniformly disperse iron ions by magnetic stirring.
[0051] 5. The mixed solution from step 3 is added dropwise to the ferric nitrate solution using a peristaltic pump, forming gel particles in the solution. During the dropwise addition of the mixed solution, the ferric nitrate solution is continuously stirred at a low speed with a magnetic force to ensure uniform dispersion of iron ions.
[0052] 6. Collect the gel particles, rinse them repeatedly with deionized water, freeze them in liquid nitrogen, and then transfer them to a freeze dryer for drying.
[0053] 7. Place the dried granules in a quartz boat, then transfer them to a tube furnace. Under inert gas protection, first sulfide and then selenide are applied. The sulfide treatment method is as follows:
[0054] In a nitrogen atmosphere, sulfur powder and dried granules were mixed at a mass ratio of 1:5 and placed in a quartz boat. The tube furnace was heated at a rate of 3.5℃ / min to 550℃ for 3.5 hours.
[0055] The selenization method is as follows: In an argon atmosphere, selenium powder is mixed with the above-mentioned sulfurized material at a mass ratio of 1:2. The heating rate of the tube furnace is 3.5℃ / min, and the temperature is raised to 700℃ for 2 hours. After the heating is completed, the material is naturally cooled to room temperature and removed to obtain a three-dimensional porous carbon-based selenide / sulfide iron composite material.
[0056] Example 3
[0057] This embodiment provides another method for preparing a three-dimensional porous carbon-based selenide / iron sulfide composite material, comprising the following steps:
[0058] 1. Solution A: Dissolve 3g of sodium alginate in 80ml of deionized water and stir for 3 hours at room temperature to ensure thorough mixing until a homogeneous solution with a certain viscosity is obtained.
[0059] 2. Solution B: Dissolve 350 mg of graphene oxide in 20 ml of deionized water and sonicate until uniformly dispersed;
[0060] 3. Mixed solution: Mix solution A and solution B at a volume ratio of 4:1 to obtain a mixed solution;
[0061] 4. Ferric nitrate solution: Prepare a 1 mol / L solution at room temperature. -1 200 mL of ferric nitrate solution was used to uniformly disperse iron ions by magnetic stirring.
[0062] 5. The mixed solution from step 3 is added dropwise to the ferric nitrate solution using a peristaltic pump, forming gel particles in the solution. During the dropwise addition of the mixed solution, the ferric nitrate solution is continuously stirred at a low speed with a magnetic force to ensure uniform dispersion of iron ions.
[0063] 6. Collect the gel particles, rinse them repeatedly with deionized water, freeze them in liquid nitrogen, and then transfer them to a freeze dryer for drying.
[0064] 7. Place the dried granules in a quartz boat, then transfer them to a tube furnace. Under inert gas protection, first sulfide and then selenide are applied. The sulfide treatment method is as follows:
[0065] In a nitrogen atmosphere, sulfur powder and dried granules were mixed at a mass ratio of 1:5 and placed in a quartz boat. The tube furnace was heated at a rate of 2.5℃ / min to 450℃ for 3 hours.
[0066] The selenization method is as follows: In an argon atmosphere, selenium powder is mixed with the above-mentioned sulfurized material at a mass ratio of 1:2. The tube furnace is heated at a rate of 2.5℃ / min, and heated to 600℃ for 2 hours. After heating is completed, the mixture is naturally cooled to room temperature and removed to obtain a three-dimensional porous carbon-based selenide / sulfide iron composite material.
[0067] Electrochemical performance evaluation
[0068] To examine the performance of the three-dimensional porous carbon-based selenide / iron sulfide composite materials in Examples 1-3 above as a negative electrode material for sodium-ion batteries, the present invention conducted the following tests:
[0069] Electrode sheets were fabricated by coating copper foil with carboxymethyl cellulose (CMC) as a binder and carbon black as a conductive additive in a mass ratio of 8:1:1, and then used for half-cell performance testing. The results of the composite material in Example 1 are as follows: Figure 2 As shown, at a current density of 3Ag -1 At that time, 370mAh g can be obtained. -1 The specific capacity is high, and it can be stably cycled for 1000 cycles; the composite materials in Examples 2 and 3 also exhibit similar properties.
[0070] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a three-dimensional porous carbon-based selenide / iron sulfide composite material, characterized in that, Includes the following steps: S1. Add the graphene oxide solution to the sodium alginate solution and mix well to obtain a mixed solution; S2. Add the mixed solution dropwise to the iron ion solution to form gel particles, collect the gel particles and dry them; S3. The dried gel particles are subjected to sulfidation and selenization reactions in sequence to obtain the three-dimensional porous carbon-based selenide / iron sulfide composite material. The vulcanization reaction is as follows: the dried gel particles are mixed with sulfur powder at a mass ratio of 1:4-6 and then calcined at 450-550 °C for 2.5-3.5 h under an inert atmosphere; The selenization reaction is as follows: the gel particles after the sulfurization reaction are mixed with selenium powder at a mass ratio of 1:1-3 and then calcined at 600-700 °C for 1.5-2.5 h under an inert atmosphere.
2. The preparation method according to claim 1, characterized in that, In step S1, the concentration of the graphene oxide solution is 75-135 g / L, the concentration of the sodium alginate solution is 18.75-37.5 g / L, and the two solutions are mixed at a volume ratio of 2-5:1 to obtain the mixed solution.
3. The preparation method according to claim 1, characterized in that, In step S2, the iron ion solution is an iron nitrate solution, wherein the concentration of iron ions is 1-3 mol / L; the volume of the iron ion solution is 1-3 times the volume of the mixed solution.
4. The three-dimensional porous carbon-based selenide / iron sulfide composite material prepared by the preparation method according to any one of claims 1-3, characterized in that, The composite material includes porous carbon nanoribbons, iron selenide, and iron sulfide; wherein, the porous carbon nanoribbons are amorphous carbon materials that are interwoven to form a three-dimensional structure, and iron selenide and iron sulfide are distributed in the three-dimensional structure.
5. The application of the three-dimensional porous carbon-based selenide / iron sulfide composite material according to claim 4 in sodium-ion batteries.
6. A sodium-ion battery negative electrode sheet, characterized in that, The three-dimensional porous carbon-based selenide / iron sulfide composite material as described in claim 1, carboxymethyl cellulose and carbon black are coated on an electrode sheet in a mass ratio of 7~9:0.8~1.2:0.8~1.
2.
7. The sodium-ion battery negative electrode sheet as described in claim 6, characterized in that, The mass ratio of the three-dimensional porous carbon-based selenide / iron sulfide composite material, carboxymethyl cellulose, and carbon black is 8:1:
1.
8. A sodium-ion battery, characterized in that, It includes the sodium-ion battery negative electrode sheet as described in claim 6 or 7.
Citation Information
Patent Citations
Metal sulfide / carbon composite material and preparation method and application thereof
CN111146424A
FeSe2-coated nitrogen-carbon-doped FeS core-shell structure composite material as well as preparation and application thereof
CN114023931A